Prevalence of anti-SARS-CoV-2 IgG positivity and long COVID-19 in pediatric age group - Hussein, Nawfal R; Khalid, Rojeen C; Jamal, Tamara B; Mahdi, Sara A; Mustafa, Abdullah S; Mohammed, Bashar I; Shukri, Mateen A; Naqid, Ibrahim A; Ameen, Rashid M (The Journal of Infection in Developing Countries, 2025)
Introduction: This study aimed to determine the prevalence and associated factors of coronavirus disease 2019 (COVID-19) and long COVID-19 in children in Duhok province and Zakho city in the Kurdistan region. Methodology: The study was conducted as a cross-sectional study and included children aged 5–12 years in Duhok and Zakho, two major neighboring cities in the Bahdenan region of northern Iraq. A total of 330 participants were included and the study was conducted between October 2022 and April 2023. The children were tested for the presence of anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG) antibodies. A questionnaire was used to collect demographic and personal data, and symptoms of each participant to determine the prevalence of long COVID-19. Results: Out of 330 participants, 302 (91.5%) were positive for IgG, and 156 (51.7%) of them were male. Only 4 participants (1.3%) had pneumonia, and 282 (93.4%) were asymptomatic. Fourteen out of 302 (4.6%) participants had long COVID-19. There were significant associations between long COVID-19 and history of previous COVID-19 episodes (p = 0.001), presence of pneumonia (p = 0.001), and family history of COVID-19 (p = 0.005). Conclusions: There was a high prevalence of COVID-19 among children in Duhok province and Zakho city, and 4.6% of them experienced long COVID-19. Factors such as prior COVID-19, pneumonia, and family history of COVID-19 were associated with long COVID-19. Continued monitoring, education, vaccination, preventive measures, and supportive care are recommended to effectively address the impact of COVID-19 on the pediatric population.